Rethinking Responses to Youth Rebellion: Recent Growth and Development of Restorative Practices in Schools. (October 2020) - Velez, Gabriel; Hahn, Madeline; Recchia, Holly; Wainryb, Cecilia
Highlights: Restorative practices are increasingly implemented in schools internationally. Current focus on discipline and behavior outcomes, perceptions of implementation. Scholarship on social development can contribute to restorative justice. Restoration may be a prosocial outlet for youth "rebellion" against unjust systems. Abstract : Adolescence has historically been framed as a time of rebellion and protest, with traditional responses in school applying punitive frameworks. In this article, we review recent psychological work on the restorative practices movement in schools as an alternative to how to respond to young people. This changing framework has implications for their development processes and can reframe some forms of rebellion as productive. We first more fully define what restorative justice entails and theoretical developments in this area. We then move to outlining interventions, programs, and associated outcomes. Finally, we end with future directions and research opportunities for psychologists.